Stokes flow in lid-driven cavity under inclined magnetic field (Archives of Mechanics - Test, 2022)
Stokes flow in a lid-driven cavity under the effect of an inclined magnetic field is studied. The radial basis function (RBF) approximation is employed to the magnetohydrodynamic (MHD) equations which include Navier–Stokes equations of fluid dynamics and Maxwell’s equations of electromagnetics through Ohm’s law with the Stokes approximation. Numerical results are obtained for the moderate Hartmann number (0 ≤ M ≤ 80) and different angles of a magnetic field (0 ≤ α ≤ π). It is found that the increase in the Hartmann number causes the development of new vortices under the main flow due to the impact of a magnetic field. However, the type of the inclination angle (acute or obtuse) determines the location of the vortices.